2008
DOI: 10.1002/jcu.20511
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial and intracranial vertebral artery dissection: Long‐term clinical and duplex sonographic follow‐up

Abstract: Recurrent TIA or stroke after VAD appears to be extremely rare, independent of recanalization or persistent occlusion of the affected artery. CDUS and TCCDUS provide reliable follow-up of VAD in all patients presenting with stenosis or occlusion, but do not allow for detection of pseudoaneurysms of the VA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
5
24
0
4
Order By: Relevance
“…7,19 In the Wessels et al series, 7 complete recanalization was found in 64% of patients, whereas De Bray et al 17 reported complete recanalization in 9 (50%) of 18 patients with intracranial VAD and in 4 (36%) of 11 with extracranial VAD. Using digital subtraction angiography as the follow-up technique, Lee et al 18 found complete recanalization in 63% of the 19 patients with VAD with a mean time to achieve complete recanalization of 8.6 months (range, 3 weeks to 56 months) by combining data from 37 VAD cases.…”
Section: Arauz Et Al Vertebral Artery Dissection 719mentioning
confidence: 97%
See 4 more Smart Citations
“…7,19 In the Wessels et al series, 7 complete recanalization was found in 64% of patients, whereas De Bray et al 17 reported complete recanalization in 9 (50%) of 18 patients with intracranial VAD and in 4 (36%) of 11 with extracranial VAD. Using digital subtraction angiography as the follow-up technique, Lee et al 18 found complete recanalization in 63% of the 19 patients with VAD with a mean time to achieve complete recanalization of 8.6 months (range, 3 weeks to 56 months) by combining data from 37 VAD cases.…”
Section: Arauz Et Al Vertebral Artery Dissection 719mentioning
confidence: 97%
“…обнаружили, что реканализа-ция происходит в основном в течение первых 6 меся-цев после появления симптомов заболевания [6]. Тем не менее изучение ДПА с помощью дуплексно-го ультразвукового сканирования остается сложной задачей из-за небольшого размера позвоночных арте-рий, их глубокого залегания, частых анатомических вариаций и особенностей близлежащих структур [7,8]. Магнитно-резонансная ангиография (МРА) и компьютерная ангиография (КТА) имеют потенци-альные преимущества в отношении неинвазивного исследования заболеваний экстракраниальных сосу-дов и ранее доказали свою полезность для выявления ДПА [9][10][11].…”
Section: (18)'2010unclassified
See 3 more Smart Citations